2001
DOI: 10.1007/s004320000225
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2: a novel target for cancer chemotherapy?

Abstract: Epidemiologic studies have documented a 40-50% reduction in incidence of colorectal cancer in individuals taking nonsteroidal antiinflammatory drugs (NSAIDs). Since NSAIDs are known to inhibit cyclooxygenases (COX-1, COX-2), the basic mechanism of their antitumor effects is conceivably the altered metabolism of arachidonic acid and, subsequently, prostaglandins (PGs). Although COX-2, the inducible isoform, is regularly expressed at low levels in colonic mucosa, its activity increases dramatically following mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
241
3
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(258 citation statements)
references
References 34 publications
6
241
3
8
Order By: Relevance
“…Intact nuclei were collected by cytospin and evaluated for ␤-catenin using fluorescently tagged anti-␤-catenin antibodies mens (34,61,62). Cox-2 contributes to tumorigenesis by inhibiting apoptosis, increasing growth factor expression to promote angiogenesis, and by enhancing matrix metalloproteinase expression to stimulate invasion (63). The membrane-anchored receptor uPAR binds urinary-type plasminogen activator and participates in cell surface-associated plasminogen activation.…”
Section: Discussionmentioning
confidence: 99%
“…Intact nuclei were collected by cytospin and evaluated for ␤-catenin using fluorescently tagged anti-␤-catenin antibodies mens (34,61,62). Cox-2 contributes to tumorigenesis by inhibiting apoptosis, increasing growth factor expression to promote angiogenesis, and by enhancing matrix metalloproteinase expression to stimulate invasion (63). The membrane-anchored receptor uPAR binds urinary-type plasminogen activator and participates in cell surface-associated plasminogen activation.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is highly inducible by the oncogenes ras and scr and other cytokines at the sites of inflammation and cancer (Kam and See, 2000;Turini and DuBois, 2002;Church et al, 2003). Previous studies have shown that most cancer cells are found to exhibit over-expression of COX-2, which can stimulate cellular division and angiogenesis and inhibit apoptosis (Dempke et al, 2001). Accumulated evidence suggests that COX-2 selective inhibitors such as non-steroidal anti-inflammatory drugs (NSAIDS) induce apoptosis by suppressing the COX-2 levels (Huang et al, 2005).…”
Section: Cox-2 and Colon Cancermentioning
confidence: 99%
“…In the last few years there have been many studies on the mechanisms involving the carcinogenesis of colorectal cancer. Inflammatory process and genetics play the key role in neoplasia of colorectal cancer .The identification of an enzyme COX-1 and COX-2, catalyzing fatty oxidation as rate limiting step in the progress from normal cell growth through hyperplasia or to neoplasia has opened up a whole new field of cancer search (Dempke et al, 2001). COX -1 and COX-2 catalyze the first stage in the oxidation of arachidonic acid to prostaglandin (Karahan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the colorectal cancers are derived from adenomas (Wu et al, 2003). It has been hypothesized that the up regulation of COX-2 prolongs the survival of abnormal cells and thereby favors the accumulation of sequential genetic changes, which increases the risk of tumorigenesis (Dempke et al, 2001). However, the over-expression of COX-2 protein in colorectal cancers is likely to occur via several different mechanisms involving complex signaling pathways, since transformed epithelial cells and stromal cells, such as mononuclear cells, fibroblasts, endothelial cells and smooth muscle cells have been shown to express increased levels of COX-2 (Sonoshita et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation